Cuarenta mitos sobre el bullying: Claves para una convivencia escolar segura - Expósito, Cristián David (2024)
This academic essay addresses the phenomenon of school bullying and its digital dimension (cyberbullying) from a critical, scientific, and pedagogical perspective. Framed within the fields of education and school psychology, the text offers a reflective analysis of social and educational discourses that tend to normalize or downplay this form of violence. Its central purpose is to identify, analyze, and dismantle the myths and misconceptions that surround it. The underlying hypothesis is that these fallacies hinder both prevention and intervention efforts by legitimizing aggressive behavior, blaming victims, or absolving adults of their responsibility to act. The methodological approach is based on a documentary and conceptual analysis of specialized literature and current regulations, complemented by a classification and critical discussion of forty prevalent myths about bullying. Each myth is contextualized, contrasted with empirical evidence, and refuted through up-to-date scientific arguments. The essay shows how the persistence of these beliefs distorts the understanding of school bullying and hinders the construction of safe environments. It concludes that debunking these myths is essential to strengthening educational intervention, empowering victims, and promoting school coexistence grounded in respect and human rights.